Narrative analysis, as a contribution to reflective practices in social work - Leiva Sandoval, Paula; Puig Cruells, Carmina (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The present work is a qualitative-descriptive research, developed for the doctoral studies in Social Work, of the Rovira i Virgili University, whose purpose is to recognize and identify the spaces of reflection of the professional work that social workers have, and the topics that arise from such reflection. Some first results and considerations on the subject are presented. Methodological advances can also be found, as well as the approach that is carried out in the field work and the connection with people who share their stories and experiences related to their professional work